The Role of cortisol in the stress response - anliana; Panguhutan Sitorus, Henry; Silitonga, Melva (Talenta Publisher, 2025)
Stress is a physiological and psychological response triggered by internal or external stressors that challenge the body's homeostasis. Cortisol, a glucocorticoid hormone released by the adrenal glands in response to stress, plays a pivotal role in modulating this response. Its primary function is to mobilize energy, regulate inflammation, and enhance cognitive processes during acute stress. While cortisol facilitates adaptation by suppressing overactive immune responses and ensuring resource availability, its prolonged elevation can lead to detrimental effects, including metabolic disorders, cardiovascular diseases, and cognitive impairments. Conversely, inadequate cortisol production disrupts the body’s ability to manage stress, resulting in conditions like fatigue, hypotension, and impaired recovery. This study explores the dynamic relationship between stress and cortisol, emphasizing how balanced cortisol levels contribute to stress resolution and homeostasis restoration. Understanding cortisol’s dual role provides insights into its potential therapeutic applications for managing stress-related disorders.